Tanggung Jawab Pemerintah terhadap Kegagalan Percetakan Sawah di Kabupaten Konawe (Studi Kepustakaan) - Rais, Noval; Akib, Ma'ruf; Hamzah, Ismi Fadjriah (Universitas Batanghari Jambi, 2024)
The Rice Paddy Printing Program in Konawe Regency, Southeast Sulawesi, aims to increase rice production for national food security, but has experienced complex failures, raising questions about the government's legal responsibilities. This research used a normative juridical method with a statutory approach, lasting for 6 months. The focus of the research is the government's responsibility for the failure of rice field printing in Konawe Regency. The main data sources include Law Number 23 of 2014 and Government Regulation Number 26 of 2008, as well as secondary and tertiary legal materials such as books, journals and internet sites. The research location is in Konawe Regency, with data collection techniques through document study and qualitative analysis. The result is an analysis of the failure of the rice field printing program in Konawe Regency, showing that the main problems are lack of coordination between agencies, lack of assistance for farmers, inadequate infrastructure, inadequate planning and weak supervision. The legal consequences of this failure include state losses due to lawsuits from farmers, as well as a decline in public trust in the government. Recommendations for improvement include strengthening coordination between agencies, increasing mentoring and empowering farmers through training, as well as building supporting infrastructure such as irrigation systems and market access.